Ion channels alterations in the forebrain of high-fat diet fed rats - Proshanta Roy (PAGEPress Publications, 2021)
Evidence suggests that transient receptor potential (TRP) ion channels dysfunction significantly contributes to the physiopathology of metabolic and neurological disorders. Dysregulation in functions and expression in genes encoding the TRP channels cause several inherited diseases in humans (the so-called ‘TRP channelopathies’), which affect the cardiovascular, renal, skeletal, and nervous systems. This study aimed to evaluate the expression of ion channels in the forebrain of rats with diet-induced obesity (DIO). DIO rats were studied after 17 weeks under a hypercaloric diet (high-fat diet, HFD) and were compared to the control rats with a standard diet (CHOW). To determine the systemic effects of HFD exposure, we examined food intake, fat mass content, fasting glycemia, insulin levels, cholesterol, and triglycerides. qRT-PCR, Western blot, and immunochemistry analysis were performed in the frontal cortex (FC) and hippocampus (HIP). After 17 weeks of HFD, DIO rats increased their body weight significantly compared to the CHOW rats. In DIO rats, TRPC1 and TRPC6 were upregulated in the HIP, while they were downregulated in the FC. In the case of TRPM2 expression, instead was increased both in the HIP and in the FC. These could be related to the increase of proteins and nucleic acid oxidation. TRPV1 and TRPV2 gene expression showed no differences both in the FC and HIP. In general, qRT-PCR analyses were confirmed by Western blot analysis. Immunohistochemical procedures highlighted the expression of the channels in the cell body of neurons and axons, particularly for the TRPC1 and TRPC6. The alterations of TRP channel expression could be related to the activation of glial cells or the neurodegenerative process presented in the brain of the DIO rat highlighted with post synaptic protein (PSD 95) alterations. The availability of suitable animal models may be useful for studying possible pharmacological treatments to counter obesity-induced brain injury. The identified changes in DIO rats may represent the first insight to characterize the neuronal alterations occurring in obesity. Further investigations are necessary to characterize the role of TRP channels in the regulation of synaptic plasticity and obesity-related cognitive decline.